Comparing effectiveness of mineral trioxide aggregate, bioceramic putty and tannic acid in maintaining pulp vitality after experimental pulpotomy in rats - Aya Anwar Alsherif; Mohamed Salah; Mai Badreldin Helal (Scientific Reports)
Abstract This study aimed to evaluate and compare the effectiveness of mineral trioxide aggregate (MTA), bioceramic putty (BP) and tannic acid (TA) for experimental pulpotomy. Our in-vivo experimental study involved sample of 45 rats that were randomly divided into 4 groups: Group 1 (subdivided into negative (1-A) and positive (1-B) subgroups), Group 2 (MTA treated), Group 3 (BP treated) and Group 4 (TA treated). 4 weeks post pulpotomy, specimens were analyzed histologically, immunohistochemically using dentin sialoprotein marker, and histomorphometrically by assessing the thickness of newly formed dentin bridge. Group 1-B showed pulp necrosis without hard tissue formation. Group 2 showed moderate dentin formation while group 3 presented a thick layer of calcific barrier. Group 4 showed dentin bridge formation, however, irregular pulp calcifications and radicular pulp necrosis were seen. The thickness of newly formed dentin bridge showed a significant difference between group 1-B and group 2, 3 &4. Significant difference was found between group 2&3 and group 3&4. Dentin sialoprotein immunohistochemical expression was negative in group 1-B, mild in group 2, strong in group 3 and moderate in group 4. MTA and BP proved to be effective pulpotomy agents with BP being superior. For TA, further studies are required to explain the recorded unfavorable effects in some specimens.